The Factors Affecting Long-Term Stability in Anterior Open-Bite Correction - A Systematic Review - Yousef Al-Thomali; Sakeenabi Basha; Roshan Noor Mohamed (Galenos Yayinevi, 2017)
Objective:The present systemic review was conducted with the main purpose to evaluate the quantitative effects of orthognathic surgeries, extraction versus non-extraction treatment, and the type of malocclusion in the stability of anterior open-bite (AOB) correction over the long-term.Methods:The systematic search for studies was conducted through MEDLINE, CINAHL, EMBASE, Scopus, PsychINFO, various key journals, and review articles; November 30, 2016, was the last date for the search. The Quality Assessment Tool for Quantitative Studies was used to grade the methodological quality of the studies.Results:The present review included 14 studies. Stability of the corrected AOB ranged from 61.9% to 100%. The studies with orthognathic surgeries showed a stability of 70-100%. The studies without orthognathic surgeries showed the stability of 61.9-96.7%. All of the studies were retrospective. The mean change in AOB before (T1) and after treatment (T2-T1) was 0.1 mm to 6.93 mm and the mean change in overbite from T2 to T3 (T3-T2) was −0.06 mm to 2.5 mm.Conclusion:Studies with orthognathic surgeries presented with high amount of long-term stability in corrected AOB. No significant difference was noticed in relation to the type of malocclusion and extraction or non-extraction cases.